Robust Identification of Parametric Radiation Force Models via Impulse Response Fitting - Hatecke, Hannes; Krüger, Stefan (Proceedings in applied mathematics and mechanics, 2015)
This paper presents a new identification method for obtaining parametric state‐space models for radiation force computation. These state‐space models can substitute the convolution integral in the equations of motion based on the impulse response function method. Thus, the method converts the integro‐differential equation to an ordinary differential equation which reduces the computational effort of radiation force computation significantly. The identification is performed in time‐domain which means that the retardation function is subject to fit. The method is verified by the application to a floating cylinder. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)